Formulation And Physical Evaluation Of Effervescent Granules Containing 70% Ethanol Extract Of Butterfly Pea Flower (Clitoria Ternatea L.) - Sulaiman , Muhammad; Abdurrahman, Abdurrahman; Afra, Fairuz Yaumi (Universitas Borneo Lestari, 2026)
Butterfly pea (Clitoria ternatea L.) is a plant commonly found in Indonesia, known to possess bioactive antioxidant properties with an Inhibitory Concentration (IC₅₀) value of 41.36 ppm. Based on this, the ethanol extract of butterfly pea flower has the potential to be formulated into effervescent granules using various concentrations of citric acid, tartaric acid, and sodium bicarbonate. This study aims to determine the effect of different concentrations of citric acid, tartaric acid, and sodium bicarbonate on the physical properties of the effervescent granules and to identify the optimal formula based on the evaluation results. The effervescent granules were formulated into four different formulas using the butterfly pea flower extract as the active ingredient and were evaluated through various physical tests. Based on organoleptic tests, all formulas exhibited a slightly sour taste, a greenish- brown color, and a distinctive butterfly pea aroma. The results of the physical evaluations showed that the compressibility index ranged from 9.41%-21.88%, flow time from 2.47-3.59 seconds, angle of repose from 29.78°-35.53°, dissolution time from 3.48-5.55 minutes, and pH values from 4.66-5.65. Based on these evaluations, it can be concluded that the variation in the concentrations of citric acid, tartaric acid, and sodium bicarbonate affects the physical characteristics of the granules. Among the tested formulas, Formula 2 demonstrated the most favorable and optimal physical characteristics compared to the others.